Secure framework for cloud data sharing based on blockchain - Figueira, André (2019)
Blockchain is a relatively new and disruptive technology that is considered a distributed database working as a ledger, with the ability to facilitate the recording of transactions and tracking of assets. It is a growing list of records called blocks linked together by the hash of the previous block, where each block contains the most recent transactions in the network. Smart contracts are agreements between entities that are written in code, and, when associated with Blockchain they will operate without interference, censorship or malicious intentions. Data Sharing on Clouds is common but requires trust on third parties to ensure various aspects, such as security and privacy, but these are unknown aspects the owner has no controls over. The Cloud Storage providers control the data access and sharing over the data. Sharing data through third party services, using unknown methods is a delicate process regarding the privacy and security aspects. These two aspects are crucial points when it comes to personal and private data. In this work, the concept of using Blockchain to create a Data Sharing mechanism is explored. This proof of concept explores how data access and permissions can be controlled using blockchain and smart contracts, by giving control to the owner and focusing on smart contracts and blockchain; Sumário: Framework Segura para Partilha de Dados em Clouds sobre Blockchain Blockchain é uma tecnologia relativamente nova e disruptiva, considerada uma base de dados distribuída e funcionando como um livro de registo. Tem a capacidade de facilitar o registo de transacções e de rastreamento de bens. É uma lista crescente de conjuntos de registos chamados blocos, ligados um aos outros através da hash do bloco anterior. Os Contractos Inteligentes são acordos entre entidades escritas em código. Quando associadados à tecnologia Blockchain operam sem qualquer inteferência de terceiros, censura ou intenções maliciosas. A partilha de dados na cloud é bastante comum mas requere confiança em terceiros para garantir que vários aspectos como segurança e privacidade são assegurados, mas estes são aspectos sobre quais o dono dos dados não tem controlo. A cloud tem controlo sobre o acesso e a partilha de dados, sendo que a partilha de dados por serviços de terceiros é um processo delicado quando se refere a privacidade e a segurança desses dados. Estes são aspectos que são cruciais quando se refere a informação pessoal e confidencial Neste trabalho, o conceito de blockchain para criar um mecanismo de partilha de dados é explorado. Esta prova de conceito explora como a partilha de dados e o controlo de acesso pode ser executados usando blockchain e contractos inteligentes. Isto dando controlo ao dono dos dados e focos em blockchain e contractos inteligentes. Permitindo que o dono dos dados seja responsável pelos seus dados.